Vidas em espera : uma etnografia sobre a experiência do tempo no processo transexualizador - Almeida, Anderson Santos (2018)
This research aims to anthropologically interpret the meanings about time and waiting among transsexual women who participate or wish to participate in the Processo Transexualizador within the Sistema Único de Saúde (SUS). I carried out fieldwork in various situations, lived with and interviewed some women participants in the Projeto Transexualidade, at Hospital das Clínicas from UFG, who shared their experiences with me. The semi-structured interviews, along with participant observation, helped me to produce the ethnographic elements that will be shared in this dissertation. Thus, among the elements that configure this research, the narratives about the (re)construction of the interviewees' body, during the so-called gender transition, stand out with a focus on time and temporality. The waiting within the public health area is constant, even more so when it comes to the quest for a better living condition and realization of dreams for trans women. This waiting can be an element that directly influences their lives, as it is a condition that is always present in each moment of life in the course of the transexualization process. Thus, at the end of this anthropological experience, it is evident to me that waiting is a factor that in many instances regulates the experiences of these women, and it is difficult to separate it from the meanings shared around the gender transition experience.